The Influence of Market Orientation, Entrepreneurial Orientation, Knowledge Management and Learning Organization on Performance Mediated by Innovation in Culinary SME’s in Bekasi - M Fadhli Nursal; Muhammad Richo Rianto; Eri Bukhari (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to see the effect of innovation mediation that connects market orientation, entrepreneurial orientation, knowledge management and organization learning on the performance of MSMEs in the city of North Bekasi. This study uses a quantitative. The unit of analysis in this study is the Culinary SMEs in North Bekasi. This research was conducted on 231 respondents spread across northern Bekasi and used the SmartPLS 3.3.3 statistical tools. The results of this study further emphasize that innovation can mediate the relationship between market orientation and performance. In addition, entrepreneurial orientation also affects performance mediated by innovation and knowledge management affects performance mediated by innovation but organizational learning has no effect on performance mediated by innovation in UMKM culinery in North Bekasi.